AQUACULTURE INSURANCE IN SUSTAINABLE FISH PRODUCTION: CASE STUDY OF NIGERIA AGRICULTURAL INSURANCE CORPORATION, OYO STATE (FULafia Journal of Science and Technology, 2019)
This study was carried out to ascertain the level of awareness and participation of stakeholders to Aquaculture Insurance in Oyo State, South-West, Nigeria. The premium ledger of the Nigeria Agricultural Insurance Corporation of the State branch was used to identify the types of agriculture insured between 2010-July 2013. Total agricultural policies paid for under review period amounts to 642 with 71 policies for Aquaculture operations ranking third, 185 Poultry second and 209 Arable first. The study revealed that the Premium received for Aquaculture Insurance amounted to ₦1,680,959:90 (US$11,206:39) during this period. Five commercial banks were responsible for all the aquaculture insurance policy undertaken.